Caracterización de hongos nativos con potencial entomopatógenos para el control de la paratrioza (Bactericera cockerelli) en condiciones de laboratorio - Abad Camacho, Damarys Lilibeth (2024)
Paratrioza (Bactericera cockerelli) attacks Solanaceae crops, causing heavy yield losses due to disease transmission. In most cases, control is done with chemical products, which leads to resistance and changes in microbial diversity. To reduce the consequences, biocontrols based on entomopathogenic fungi can be implemented. For this reason, the objective of this study is to isolate and characterize fungi with entomopathogenic potential for the control of paratrioza under laboratory conditions. For this purpose, fungal samples were collected in the canton of Loja and taken to the Plant Health Laboratory of the National University of Loja for analysis. The technique of serial dilutions was carried out, which were sown in PDA medium and incubated at 25 °C to 28 °C. The fungal samples were purified and subjected to replating. Subsequently, cultural (appearance, surface, color) and morphological (radial growth rate, colony forming units, conidia size) characterization was performed. Additionally, the virulence of the two entomopathogenic fungi and a chemical control on B. cockerelli was evaluated on bell pepper plants. The results indicate the obtaining of two isolates Lecanicillium spp. (L) and Beauveria spp (B), which presented the following characteristics: Radial Growth Rate of 0.458 - 0.53 mm/day, a size of L. 3.28 (length) x 2.2 mm (width), B. 4.40 (length) x 3.58 mm (width) and conidia of L. (5.94 x107), B (1.24 x106) and B (1.24 x106) ). For the control of Paratrioza adults, the Lecanicillium treatment controlled 91.88%, Beauveria with 90.41% and the chemical control stood out with 98%. This shows that the fungi under study can be used for a biological control program.